HaloTag‐Targeted Sirtuin‐Rearranging Ligand (SirReal) for the Development of Proteolysis‐Targeting Chimeras (PROTACs) against the Lysine Deacetylase Sirtuin 2 (Sirt2) - Schiedel, Matthias (John Wiley and Sons Inc., 2020)

(untitled) (Chembiochem)
We have discovered the sirtuin‐rearranging ligands (SirReals) as a novel class of highly potent and selective inhibitors of the NAD(+)‐dependent lysine deacetylase sirtuin 2 (Sirt2). In previous studies, conjugation of a SirReal with a ligand for the E3 ubiquitin ligase cereblon to form a so‐called proteolysis‐targeting chimera (PROTAC) enabled small‐molecule‐induced degradation of Sirt2. Herein, we report the structure‐based development of a chloroalkylated SirReal that induces the degradation of Sirt2 mediated by Halo‐tagged E3 ubiquitin ligases. Using this orthogonal approach for Sirt2 degradation, we show that other E3 ligases than cereblon, such as the E3 ubiquitin ligase parkin, can also be harnessed for small‐molecule‐induced Sirt2 degradation, thereby emphasizing the great potential of parkin to be used as an E3 ligase for new PROTACs approaches. Thus, our study provides new insights into targeted protein degradation in general and Sirt2 degradation in particular.